IShLAB ChIQARIShDA INNOVATSION TEXNOLOGIYALARDAN FOYDALANIShDA MUHANDISLIK FANLARINING IJTIMOIY AHAMIYATI - Hasanov, Q.X. (SCIENCE and SOCIETY, 2025)
The article reveals the role and importance of engineering sciences in helping students studying in the fields of production and engineering achieve great success in their fields. It also shows the role of modern knowledge in engineering sciences in raising the engineering work of our country to a new level.
Keywords: social engineering; innovative approach; production engineering; creative thinking; creative project